Access to continued-use medication among older adults, Brazil - Viana, Karynna Pimentel; Brito, Alexandre dos Santos; Rodrigues, Claudia Soares; Luiz, Ronir Raggio (Revista de Saúde Pública, 2015)
OBJECTIVE To determine the prevalence and associated access factors for all continued-use prescription drugs and the ways in which they can be obtained.METHODS Data was obtained from the 2008 Household National Survey. The sample comprised 27,333 individuals above 60 years who reported that they used continued-use prescription drugs. A descriptive analysis and binary and multiple multinomial logistic regressions were performed.RESULTS 86.0% of the older adults had access to all the medication they needed, and among them, 50.7% purchased said medication. Those who obtained medication from the public health system were younger (60-64 years), did not have health insurance plans, and belonged to the lower income groups. It is remarkable that 14.0% of the subjects still had no access to any continued-use medication, and for those with more than four chronic diseases, this amount reached 22.0%. Those with a greater number of chronic diseases ran a higher risk of not having access to all the medication they needed.CONCLUSIONS There are some groups of older adults with an increased risk of not obtaining all the medication they need and of purchasing it. The results of this study are expected to contribute to guide programs and plans for access to medication in Brazil.